2023
DOI: 10.1200/jco.22.00070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 Pandemic on Place of Death Among Medicaid and Commercially Insured Patients With Cancer in Washington State

Abstract: PURPOSE The COVID-19 pandemic–related disruptions in health care delivery might have affected end-of-life care in patients with cancer. We examined changes in place of death and hospice support for Medicaid and commercially insured patients during the pandemic. PATIENTS AND METHODS We linked Washington State cancer registry records with claims from Medicaid and two commercial insurers for patients with solid tumor age 18-64 years. The study included 322 Medicaid and 162 commercial patients who died between Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…For example, Medicaid patients from Washington were more likely to die in a hospital or without hospice services. 5 Our study finds that pandemic-related disruptions to place of death trends are ongoing, national, and extend to non–COVID-19–related diagnoses. Our study is limited by the imperfect classification of the place of death variables within the CDC WONDER database, including ambiguity regarding how assisted living facilities should be classified.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…For example, Medicaid patients from Washington were more likely to die in a hospital or without hospice services. 5 Our study finds that pandemic-related disruptions to place of death trends are ongoing, national, and extend to non–COVID-19–related diagnoses. Our study is limited by the imperfect classification of the place of death variables within the CDC WONDER database, including ambiguity regarding how assisted living facilities should be classified.…”
Section: Discussionmentioning
confidence: 59%
“…Prior studies showed how COVID-19 exacerbated access issues at the end of life immediately after the onset of the pandemic. For example, Medicaid patients from Washington were more likely to die in a hospital or without hospice services . Our study finds that pandemic-related disruptions to place of death trends are ongoing, national, and extend to non–COVID-19–related diagnoses.…”
Section: Discussionmentioning
confidence: 64%
“…Indeed, for patients with the lowest SES, home deaths increased only among those without SPC support during the month before death. A similar inequity was demonstrated in a US study: for Medicaid-insured (but not commercially insured) patients with advanced cancer, place of death shifted from hospital to home without hospice during the first 4 months of the COVID-19 pandemic . The relative increase in home deaths unsupported by SPC or hospice among socioeconomically disadvantaged populations during the COVID-19 pandemic could be due to patients wanting to avoid inpatient care but lacking access to or knowledge of end-of-life resources that would normally facilitate and support a home death.…”
Section: Discussionmentioning
confidence: 99%
“…3 During the Covid-19 pandemic, important changes in the place of death were observed in different countries. [4][5][6][7][8] In the UK, there was a sustained increase in home deaths. 5 Very little is understood about the characteristics of people who died at home during the pandemic, and how they differed compared to pre-pandemic time periods.…”
Section: Introductionmentioning
confidence: 99%